Co-expression of neighbouring genes in Arabidopsis: separating chromatin effects from direct interactions - Chen, Wei-Hua (BioMed Central, 2010)
BACKGROUND: In all eukaryotic species examined, genes that are chromosomal neighbours are more similar in their expression than random gene pairs. Currently, it is still unclear how much of this local co-expression is caused by direct transcriptional interactions, and how much is due to shared chromatin environments. RESULTS: We analysed neighbouring genes in Arabidopsis thaliana. At large intergenic distances (>400 bp), divergently and convergently transcribed gene pairs show very similar levels of co-expression, mediated most likely by shared chromatin environments. At gene distances below 400 bp, co-expression is strongly enhanced only for divergently transcribed gene pairs, indicating bi-directional transcription from a single promoter. Conversely, co-expression is suppressed for short convergently or uni-directionally transcribed pairs. This suppression points to transcriptional interference concentrated at the 3' end, e.g., in the context of transcription termination. CONCLUSIONS: Classifying linked gene pairs by their orientation, we are able to partially tease apart the different levels of regional expression modulation. (i) Regional chromatin characteristics modulate the accessibility for regulation and transcription, regardless of gene orientation; the strength of this chromatin effect can be assessed from divergently or convergently transcribed distant neighbours. (ii) Shared promoter regions up to 400 bp in length enhance the co-expression of close bi-directional neighbours. (iii) Transcriptional interference of close neighbours is concentrated at the 3' ends of genes, and reduces co-expression on average by 40%.